2018
DOI: 10.1159/000492376
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Outcomes after Transmastoid Plugging of Superior Canal Dehiscence

Abstract: Background: Patients with a superior canal dehiscence syndrome display symptoms of the vestibular disorder except that of hearing loss. Therefore, any type of surgery should treat those symptoms without affecting the hearing threshold. The aim of this study was to evaluate the extent to which the hearing threshold has been affected; the evaluation process was carried out by a transmastoid plugging of the superior canal. Another aim was to estimate the risk in loss of hearing due to this surgery. Material and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Multiple subsequent studies, however, have confirmed that transmastoid canal occlusion in the context of BPPV or superior semicircular canal dehiscence is effective in providing vertigo relief while preserving hearing. 9,10 There remains a paucity of quantifiable vestibular data in human subjects to support the subjective improvements reported. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Multiple subsequent studies, however, have confirmed that transmastoid canal occlusion in the context of BPPV or superior semicircular canal dehiscence is effective in providing vertigo relief while preserving hearing. 9,10 There remains a paucity of quantifiable vestibular data in human subjects to support the subjective improvements reported. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Patients with synchronous SSCCD are an even more complex subset of CHL. BC increased (deteriorated) in the low frequencies postoperatively in all ears with SSCCD in this series-a common finding after SSCCD repair owing to normalization of the suprathreshold BC (29,30). Although an accompanying improvement in low-frequency AC is often said to result in a decrease in, or even closure of the ABG, substantial interpatient variability has been documented.…”
Section: Discussionmentioning
confidence: 68%
“…Transmastoid plugging of the semi-circular canals is one surgical option in patients with vestibular symptoms caused by the canal dehiscence syndrome or benign paroxysmal vertigo, as conservative medical treatment is limited. Results from human studies show that vertigo control can be achieved via semi-circular canal plugging, and hearing is not affected [15]. Several studies showed that in 10% to 35% of patients with single-sided Menière's disease, so-called silent contralateral endolymphatic hydrops can be detected [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The area of each canal was covered afterward with a muscle patch and bone pate. Finally, the sealing patch was secured with fibrin glue (Figure 4) [5,15]. The subjective and objective vestibular findings were assessed preoperatively, directly postoperatively, as well as 6-8 weeks and 6 months after surgery.…”
Section: Methodsmentioning
confidence: 99%